Advanced Study on Electrically Operated Multipurpose Trolley - Al Sult Al Kharusi; Dinesh Keloth Kaithari; Parimal S. Bhambare (Advanced Aspects of Engineering Research Vol. 3, 2021)
Present paper deals with design and fabrication of industrial trolley which can be used to transfer luggage or items from one place to another place. A trolley nowadays is important for transferring different items from place to place in our daily life or even in working life as per the requirement. Depending on what is to be transported, trolleys can be plastic, metal or wooden. Wheel type and size can also vary depending on the types of ground the trolley is traveling over and the work environment. We can see trollies in shopping mall, airport and industries for handling the goods. In the airport, passengers use trollies to transfer their luggage till the check in counters. Sometimes they face higher weight issues at the check in, making them pay the excess baggage charge or dispose of few important items thereof only. This creates an uncomfortable and awkward situation at the check in. And if the passenger is an old age or senior citizen it’s really a very panic situation. Additionally, a survey based on a prepared questionnaire carried out at Muscat airport revealed the need for substantial improvements in the present trollies in terms of comfort in luggage handling, loading and unloading of the luggage and the need for weight of the luggage at the time of loading itself. Furthermore, many food and kitchen industries use trollies to receive and transfer the goods items to the store after weighing them. The Arduino based electronically operated steerable trolley developed here aims to address few of these key issues by measuring the weight of the items directly from the trolley with easy movement by electrical power from battery. The trolley has been designed using AUTOCAD and stress analysis of the structure has also been performed using CREO V3. The fabrication is completed as per the design and tested for its performance. The testing performed on the trolley shown that for the maximum load of 90 kg including the passenger weight, the time taken by the trolley to travel on a smooth horizontal airport surface for covering a distance of 10 m with full and half rated speed of motor is 7 seconds and 9.6 seconds only respectively. The trolley was also successfully tested for elevated slope at the Muscat airport requiring additional 25 seconds more at the full rated speed at maximum loading condition of 90 kg. Additionally, the trolley provides few added benefits such as charging of smart devices by using photovoltaic system technology and sliding platform for easy loading and unloading of the goods. Various drawbacks which were present in the conventional trolleys such as excessive human labor and more time involvement were reduced. The future work includes use of lighter aluminum alloy material along with use of solar panels for operation of the trolley.